"Personal information of privacy nature" under Chinese Civil Code. Issue 43 (November 2021) - Zhang, Lu
Abstract: Chinese Civil Code separates the civil right to privacy and the civil interest of personal information through the proposal of the PIPN in Article 1034, which constructs a different model from both EU and US. Although this distinction is of great significance, it brings potential problems, too. The PIPN is a kind of personal information which is unwilling to be known to others with privacy nature, which can be defined through a method of combining basic definition plus enumerations. It is recommended to consider the context and purpose of processing personal information when deciding the PIPN, and the level of privateness, availability, risk and identifiability will be considered to the privacy test. Based on Chinese reality, ID number, biometric information, financial information should be list as the typical kinds of the PIPN in the future legislation.